Don Quijote. - de Cervantes, Miquel (Rotterdam : Witte de With Center for Contemporary Art Rotterdam, 2006)
Beutler, Michael ; Billing, Johanna ; de Boer, Manon ; Byrne, Gerard ; Gander, Ryan ; Greenfort, Tue ; Hunt, William Holman ; Johne, Sven ; Kelm, Annette ; Schinwald, Markus ; Lieske, David ; Just, Jesper ; Moppett, Damian ; Moukarbel, Chris ; Navarro, Iván ; Orr, Christopher ; Pijnappel, Pablo ; Raidpere, Mark ; Rickards, Hannah ; Smith, Anj ; Velonis, Kostis ; Walker, Richard T.
Engels
Nederlands
Exhibition. Don Quijote. Witte de With Center for Contemporary Art Rotterdam, 30.04.2006 - 06.08.2006
boek